A 6-year longitudinal study: Are maternal depressive symptoms and Selective Serotonin Reuptake Inhibitor (SSRI) antidepressant treatment during pregnancy associated with everyday measures of executive function in young children?. (January 2019) - Hutchison, Sarah M.; Mâsse, Louise C.; Brain, Ursula; Oberlander, Tim F.
Abstract: Background: Building on research reports that early and chronic exposure to maternal depressive symptoms (MDS) adversely affects children's developing executive function (EF), this longitudinal study examined whether exposure to MDS and Selective Serotonin Reuptake Inhibitor (SSRI) antidepressant treatment during pregnancy predicted individual differences in EF at school age. Methods: In a longitudinal prospective cohort, maternal report of EF using the Behavior Rating Inventory of EF (BRIEF) was obtained from 139 children (77 females; non-exposed n = 88, SSRI exposed n = 51) at age 6 years. Clinician rated and self reports of MDS were also obtained spanning from the 2nd trimester to 6 years postpartum. Results: Higher levels of MDS, especially at 3 years, were associated with poorer maternal reports of EF skills at 6 years. Associations between prenatal SSRI exposure and EF outcomes were not significant, even when controlling for maternal education and MDS at 3 years. Conclusions: Postnatal exposure to MDS adversely effects developing child EF, even when maternal symptoms were treated with an SSRI antidepressant. Highlights: The impact of prenatal antidepressant treatment on everyday executive function (EF) in children is not known Maternal depressive symptoms (MDS) are associated with poorer performance on EF tasks in young children Despite prenatal antidepressant treatment, maternal reports of EF in school age children remain at risk due to ongoing MDS Future longitudinal studies are needed to determine relations between MDS, antidepressant treatment and EF in adolescents